Management of Functional Literacy Programs: The Role of Funding, Learning Community Participation, and Learning Resources - Ofri Somanedo; Any Diana Vitasari; Tegar Anggi Handika (CV Edujavare Publishing, 2026)
The Functional Literacy Program requires adequate resource management to support the achievement of student competencies. This study aims to analyze the role of funding, student participation, and learning resources in the management of the Functional Literacy Program in Antirogo Village, Sumbersari District, Jember Regency. The study used a quantitative approach with a survey method. The study population was 158 students spread across ten study groups, with a sample of 61 respondents determined through proportionate stratified random sampling. Data were collected using a closed questionnaire that measured funding components, student participation, learning resources, and literacy achievements including reading, writing, arithmetic, speaking, and listening skills. Data were analyzed using descriptive statistics, correlation, and simple linear regression at a significance level of 5%. The results showed that all three components had a significant relationship with the achievements of the Functional Literacy Program. Funding contributed the most, at 32.2% with a correlation value of 0.567, followed by student participation at 27.2% with a correlation value of 0.522, and learning resources at 22.9% with a correlation value of 0.478. All relationships had a significance value of 0.000. Descriptively, students also responded positively to all three components, especially regarding the accuracy of funding targets and involvement in overcoming personal problems. These findings indicate that the management of the Functional Literacy Program needs to integrate targeted funding, active student participation, and contextual learning resources to support the sustainability and achievement of the program.